Engineers - Farndon, John; Hart-Davis, Adam (DK Publishing, 2012)
Presents a history of the world's most prominent and revolutionary engineers, discussing their key feats and major breakthroughs, from Archimedes and Leonardo da Vinci to Henry Ford and the Wright brothers.